2003
DOI: 10.1093/geronb/58.1.s2
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and Health Care Expenditures: The Real Reasons Older People Spend More

Abstract: Both increases in the absolute number of elderly persons and in their longevity will increase future Medicare expenditures. Yet, the expected increase in per person health care expenditures caused by greater longevity of Medicare beneficiaries will be less than expected because of the concentration of expenditures at the end of life rather than during extra years of a relatively healthy life. The latter conclusion may be altered, however, because of other underlying considerations, such as technological change. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
165
2
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(197 citation statements)
references
References 10 publications
16
165
2
12
Order By: Relevance
“…The pattern of decreasing cost ratio of decedents to survivors shown in Figure 4 is similar to other studies [34,31]. This suggests that, in terms of medication, the cost of dying relative to surviving actually decreases with age.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The pattern of decreasing cost ratio of decedents to survivors shown in Figure 4 is similar to other studies [34,31]. This suggests that, in terms of medication, the cost of dying relative to surviving actually decreases with age.…”
Section: Discussionsupporting
confidence: 84%
“…Studies looking at total health care expenditures have reported increasing expenditures with age [34,12] with some attributing it to proximity to death [10,31,35]. This study has focused on prescribing expenditures and found that they do not steadily increase with age for the older population even before accounting for PTD.…”
Section: Discussionmentioning
confidence: 84%
“…16 While workload (dashed line, Fig. 2) may gradually increase as a person approaches death, 22,23 physical and cognitive capacity (solid line, Fig. 2) to manage this workload gradually decreases.…”
Section: Common Factors and Common Gaps Across Modelsmentioning
confidence: 99%
“…Cette hausse, si elle n'est pas uniforme (elle a été plus forte pour les tranches d'âges élevés 6 ), ne peut s'expliquer par des évolutions démographiques, puisqu'on raisonne par tête et à âge donné. C'est donc du côté des détermi-nants non démographiques des dépenses de santé que s'est tournée la recherche [17,18]. Des travaux en épidémiologie et en économie ont établi qu'à un âge donné, l'état de santé est bien meilleur aujourd'hui qu'il y a un siècle [19].…”
Section: Les Déterminants Non Démographiques De La Dépense De Santé Iunclassified